VARIASI LEKSIKAL DALAM BAHASA DAYAK DI KABUPATEN KETAPANG - Rianti, Lusia Tania Lisa; Patriantoro, Patriantoro; Seli, Sesilia; Priyadi, Totok; Saman, Sisilya (Jurnal Kajian Pembelajaran dan Keilmuan, 2024)
This study aims to describe lexical variations in the Dayak language in Ketapang regency.   The Dayak languages referred to are Kayong Dayak, Gerunggang Dayak, Left Pesaguan Dayak, and Upper Pesaguan Dayak. This research resulted in differences in the lexical variations of the Dayak language found in the Districts of Nanga Tayap, Pemahan, and Tumbang Titi. The problem in this study, namely how are lexical variations, mapping in the Dayak language, and semester lesson plans in morphology courses in the Indonesian Language Education strata 1 program. The method used is descriptive, listening, and proficient in the form of qualitative and quantitative research. The data sources in this study include four Dayak languages. Data collection techniques, namely tapping techniques, engaging listening techniques, recording, note-taking, fishing, and conversing techniques. The tool used in this research is a list of questions that contain 537 glosses. Based on the results of the data in this study, 209 lexical variations were found from 537 lists of questions asked. There are 209 maps containing lexical data. The map contains lexical glossal data with a symbol system. The level of language variation between observation points found in the Dayak language is different speech, different sub-dialects and different dialects. Semester lesson plans in morphology courses in the Indonesian Language Education strata 1 program.